Enhancing Speaking Skills through Digital Storytelling: A case study - Alaiksander, Abdurrasyiid; Rokhayani, Atik; Sulistyowati, Titis (Prodi Pendidikan Bahasa Inggris, FPBS, Universitas PGRI Semarang, 2026)
This research assessed how digital storytelling (DST) could enhance the junior high school students' oral proficiency skills in speaking the English language in the context of Islamic schooling in Indonesia. The research deployed a quasi – experimental design within the context of an Islamic school setting. The sample consisted of 64 students. 31 students comprised the experimental class who received instruction through the use of DST while 33 students made the control class who were taught using traditional instructional techniques. The data was collected through administered tests which assessed the students' speaking through various parameters. To understand the progress of the student's scores within the two groups the Wilcoxon signed-rank test was utilized. It was found out that all of the students improved in their speaking skills but the experimental group had higher scores. This shows DST has a high positive effect on students’ oral performance. DST gave positive impact on student's enthusiasm, teamwork and confidence in using the language was also noted. The students’ level of DST speaking discipline was high which suggests the technique is useful. The implications of this study point towards DST to strengthen the students’ motivation, performance and speaking competency.